The phenomenon of overkill in northern Greece: A descriptive forensic psychiatric study between 2015 and 2020 on criminal offenders found not guilty by reason of insanity. (August 2022) - Karakasi, Maria-Valeria; Markopoulou, Maria; Nikolaidis, Ioannis; Voultsos, Polychronis; Avramidis, Athanasios; Nastoulis, Evangelos; Fotou, Eleni; Douzenis, Athanasios; Pavlidis, Pavlos
Abstract: The purpose of this descriptive study was to investigate overkill in a representative sample of Greek psychiatric patients found not guilty by reason of insanity (NGRIs) from a forensic psychiatric - criminological standpoint and explore possible correlations of the phenomenon with socio-cultural or psychiatric factors. Overall, 24 forensic psychiatric records of overkill offenders were identified throughout the 5-year records of the national forensic psychiatric service in northern Greek mainland. The pattern that has emerged from the statistical results of the present study on the victims of overkill within the Greek borders was generally in line with global literature on homicide perpetrators. The mean age of overkill offenders (at the time of enactment of the crime) was estimated at 36.3 years ranging from 19 to 55 years (variance = 146.72; standard deviation = 12.11). The number of male single-offence killers was ten-times larger compared to their female counterparts, while the number of male multiple-offence killers were three-times larger compared to their female counterparts. Male offenders were averagely 15 years younger (mean 33.7; variance = 81.69; standard deviation = 9) in comparison to female offenders, and single-offence killers were averagely ten years younger compared to multiple-offence killers (mean 40.2; variance = 185.19; standard deviation = 13.6). The phenomenon correlated more strongly with homicides in the context of schizophrenia spectrum disorders (80–100%) as well as domestic violence. Overall, males outnumbered females both as offenders (approximately five-times) and victims (approximately three-times), but regarding domestic violence, the sad majority of overkill victims stood for females murdered by their male relatives. Close female relatives (especially mothers and grandmothers) were most often victimized. Female-perpetrated overkill was directed against male individuals with whom offenders shared a relationship (intimate partners and minors). An important finding was the fact that three-quarters of the overall perpetrator sample were under prescribed medication at the time of offence, but with a very low compliance rate (5.6%). This last particular finding of the present study demonstrated that mental health services within community in Greece may unfortunately have been ineffective in addressing issues requiring risk assessment and timely intervention. Highlights: Overkill NGRI-offenders in Greece are investigated via a 5-year descriptive study. Psychopathology correlated strongly with schizophrenia spectrum disorders. Males and multiple-offence killers were found to overall outnumber counterparts. Mothers and grandmothers were mostly victimized in domestic homicide cases. Most offenders were under prescribed medication at the time of offence.